THE IMPACT OF APPLYING MATA VERSE TECHNOLOGY ON HUMAN RESOURCES COSTS IN THE PRESENCE OF ENVIRONMENTAL UNCERTAINTY AS AN INTERACTIVE VARIABLE, AN APPLIED STUDY IN THE BANKING INDUSTRY SECTOR - Assistant Professor Zainab J. Yusuf; Professor Dr Suhail Abdullah Al-Tamimi (Galaxy International Interdisciplinary Research Journal, 2024)
This study aims to identify the impact on the human resources costs when applying meta verse technology in the banking industry sector, as banking sector is viewed to be one of the sectors that tend to follow technology and use it to address some of the problems it faces. Through a number of channels, such as user engagement and participation in activities that often occur in the real world, meta verse technology may expeditiously and dependably resolve issues for users of a service in a virtual environment. This technology saves time and effort and is an effective way, to simulate reality, whatever its circumstances and difficulties, and provide opportunities to communicate with people we do not know in our real life and help form new relationships more efficiently compared to real-life questionnaire form was organized for a random sample of governmental and private banks for a sample of 136. The groups included in the sample are senior management, individuals working in current accounts, individuals working in savings accounts, and bank customers who have current accounts with the bank. Many conclusions have been reached, including there is a fear of the application of Meta verse due to the difficulty of proving ownership in Meta verse, and this requires seeking technical and legal to reach a safe way to prove ownership and transfer it.